Otaku : produção de sociabilidade entre jovens mato-grossenses - Coutinho, Kesley Gabriel Bezerra (2022)
The process of sociocultural approximation, in convergence with a global frenzy of multiple and constant transformations, establishes in contemporary times a new panorama of connection and production of meaning with life, of being at the heart of social complexities. Japanese artisticcultural productions, animê and mangá, in this segment, appear at the end of the 20th century and establish new contours in the sociability relations of Brazilian young adults, in a diverse subjective production, translating into an otaku identity. The project intends to investigate the ways and circumstances in which the production of sociability of these individuals takes place in Cuiabá and surrounding regions. The understanding and analysis of this project is outlined through the ethnographic theoreticalmethodological positioning, in a qualitative practice of immersion anchored in experience, in a participant observation of rites, games, performances and rituals. Japanese artistic productions, animê and mangá, present us with positive ways of producing sociability and point to a logic of difference, of connection with life and escape from normativities.